Hannah Arendt’s Revolutionary Leadership - LeJeune, John (HannahArendt.net, 2013)
The year 2011 saw the rise of “leaderless” models of protest spurred by the tactical use of diffuse social media to mobilize bodies, and the political pursuit of a more radically democratic and egalitarian politics in the face of rampant elite-class corruption. Occupy called itself a “leaderless resistance movement,” and the Egyptian revolution was touted “because it had no leaders, only coordinators of bottom-up energy.” To theorize the “power” of leaderless movements and give normative weight to principles of “non-representation,” scholars and activists often turned to Hannah Arendt. I argue, however, that Hannah Arendt’s political theory offers little normative or theoretical support for a politics of "leaderless revolution." To the contrary, Arendt highlights the importance of reifying power in the streets into political institutions, as well as leadership’s critical role in effecting this process in the interest of freedom. Hardly a path towards democratic founding, the ideal of leaderlessness represents a dangerous turn towards the absence of genuine political responsibility.